2016
DOI: 10.1002/acm2.12012
|View full text |Cite
|
Sign up to set email alerts
|

Organ motion in pediatric high‐risk neuroblastoma patients using four‐dimensional computed tomography

Abstract: Purpose/objective(s)High‐risk neuroblastoma (HR‐NBL) requires multimodality treatment, including external beam radiation of the primary tumor site following resection. Radiotherapy planning must take into account motion of the target and adjacent normal anatomy, both of which are poorly understood in the pediatric population, and which may differ significantly from those in adults.Methods/materialsWe examined 4DCT scans of 15 consecutive pediatric patients treated for HR‐NBL, most with tumors in the abdominal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Pai Panandiker et al have reported an average of 5.1 mm (range: 3.0-10.0), although the distinction between the left and right was not specified [ 6 ]. Kannan et al have reported 4.4 ± 2.0 mm on the right and 3.6 ± 2.3 mm on the left [ 8 ]. Uh et al examined 35 cases and summarized the results in detail for each case [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Pai Panandiker et al have reported an average of 5.1 mm (range: 3.0-10.0), although the distinction between the left and right was not specified [ 6 ]. Kannan et al have reported 4.4 ± 2.0 mm on the right and 3.6 ± 2.3 mm on the left [ 8 ]. Uh et al examined 35 cases and summarized the results in detail for each case [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports of pediatric respiratory-induced position variations in NBL have been presented [4][5][6][7][8][9][10][11][12][13]. However, reports were limited to four facilities; of these, only one facility reported from Asia, and it is hard to say that a global consensus has been reached regarding the setting of internal margin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to these general considerations, a recently published study has shown how high the interobserver variability is in determining the operating plan [33]. Over time, radiotherapy techniques have advanced considerably, introducing image-guided, high-precision irradiation, and proton beam therapy to the field of neuroblastomas [34][35][36]. Therefore, exact three-dimensional tumor detection could be increasingly relevant for high-precision irradiations of neuroblastomas as it had already occurred in CNS disease [37,38].…”
Section: Discussionmentioning
confidence: 99%